Inequality in Vietnamese urban-rural living standards, 1993 - 2006 - Huong Thu Le; Alison L. Booth (Institute for the Study of Labor (IZA), 2010)
Using data from five waves of the Vietnam Household Living Standard Survey, we find evidence of significant urban-rural expenditure inequality. Urban-rural inequality in Vietnam increased dramatically from 1993 to 1998, and peaked in 2002 before reducing slightly in 2004, and significantly in 2006. The urban-rural gap also monotonically increases across the expenditure distribution. We use a variant of the Oaxaca-Blinder decomposition method, applied to the unconditional quantile regression method of Firpo, Fortin and Lemieux (2009), to explain the components of the per capita expenditure differentials between urban and rural households at selected quantiles of the distribution. We also compare these estimates with those at mean obtained by OLS. Our results show a number of factors contributing significantly to the high urban-rural gap. These include inter-group differences in education, household demographic structure, industrial structure and their related returns. Adjusting the average characteristics of rural households to those of urban households will reduce about a half of the overall urban-rural expenditure gap. A significant part of the remaining unexplained component lies in the intercept differences; that is, the inter-group differences in other factors not captured in the model that favor urban households.
Keywords: O18; O53; C13; 330; Urban-rural inequality; Vietnam; unconditional quantile regression; Oaxaca decomposition; Regionale Disparität; Ländlicher Raum; Stadt; Verbraucherausgaben; Soziale Ungleichheit; Vietnam